The Importance of External Communication in Strengthening Relations Between a Sports Organisation and Its Stakeholders: The Case of Kaunas Amateur Volleyball League - Taraskevičius, Adomas; Grigalaitis, Edvinas (Vilnius University Open Series, 2025)
In order to get closer to the fans, to gain more public attention, and to increase the popularity of the sport, sports organisations inevitably have to focus on external communication. Increased visibility often leads to a wider range of financial supporters, while increased funding also allows the sport organisation itself to grow. Kaunas Amateur Volleyball League (KAVL), as an active sports organisation, faces challenges in reaching its audience – both participants and spectators – therefore it is necessary to identify the existing problems in the organisation’s external communication and to identify ways to improve it. The effectiveness of KAVL’s external communication on the League’s Facebook account and website was analysed by means of quantitative and qualitative content analysis and a questionnaire survey. The analysis showed that KAVL provides a lot of detailed information about the upcoming events as well as results, publishes a high amount of news, keeps the information up-to-date, but the posts are irregular, with numerous errors and low user engagement. The website was found to be rich in information, but its design is outdated and unattractive. The article concludes that KAVL needs to pay more attention to the quality of the presentation of information and the interaction on social networks with the followers and fans. Also, the lack of a content calendar results in inconsistent communication within KAVL. A posting schedule would allow for a systematic planning of when and which posts to publish, and an update of the website would also contribute to improving the overall image of the League and would help to attract a larger audience of fans.